Digital Applications: True Means of Communication and digital Transformation Les Applications Numériques: Véritables Moyens de Communication et De Transformation Numérique - Bouri, Nassima (Finance and Business Economies Review, 2019)
Digital applications are powerful means of communication and digital transformation because they enable brands to achieve their overall communication goals. The growth of different techniques has changed the strategies of production, distribution, intermediation and even consumption of products and services. In digital marketing, these digital applications allow brands to engage with a large number of Internet users and promote themselves in a digital environment. The main objective of this article is to explain the link between the management of companies and digital and computer applications in economic and managerial activities, as well as the position of the Algerian system in this context.